2001
DOI: 10.1007/s002560100412
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing multiple rice body formation in chronic subacromial-subdeltoid bursitis from synovial chondromatosis

Abstract: Multiple rice body formation is a complication of chronic bursitis. Although it resembles synovial chondromatosis clinically and on imaging, the literature suggests that analysis of radiographic and MR appearances should allow discrimination. We report the imaging findings in a 41-year-old man presenting with rice body formation in chronic subacromial-subdeltoid bursitis. We found that the signal intensity of the rice bodies is helpful in making the diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 8 publications
1
35
0
1
Order By: Relevance
“…[11] Some investigators have suggested micro infarctions after intra-articular synovial inflammation and ischemia, with subsequent synovial shedding and encasement by fibrin derived from synovial fluid as a possible cause. [4,12] Nonetheless, de novo formation and progressive enlargement by fibrin is also a possible mechanism [3], and an alteration in fluid viscosity and fibrinogen content of the synovial fluid has been implicated.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Some investigators have suggested micro infarctions after intra-articular synovial inflammation and ischemia, with subsequent synovial shedding and encasement by fibrin derived from synovial fluid as a possible cause. [4,12] Nonetheless, de novo formation and progressive enlargement by fibrin is also a possible mechanism [3], and an alteration in fluid viscosity and fibrinogen content of the synovial fluid has been implicated.…”
Section: Discussionmentioning
confidence: 99%
“…On MRI, rice bodies have been described as having iso-or hypointense signal intensities relative to skeletal muscle on T1-and T2-weighted images, and the rice bodies were less discernible from the surrounding bursa fluid on T1-weighted image and clearly discernible on T2-weighted image. [3][4][5] Synovial chondromatosis was a differential diagnosis in the above case. Synovial chondromatosis usually has an iso-intense or slightly hyperintense signal intensity on T1-weighted image, and hyperintense signal intensity on T2-weighted image relative to the signal intensity of skeletal muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Cheung et al suggested synovial origin with micro-infarction of synovial cells after inflammation and ischaemia,¹ whereas Popert et al proposed a de novo formation of rice bodies in synovial fluid independently of synovial elements.² Formation of rice bodies has been reported in joints, 1,2 bursae 3-6 and tendon sheaths, 5 and are commonly observed in chronic rheumatoid arthritis, seronegative inflammatory arthritis and tuberculous joints. 3 Different-shaped rice bodies are described, varying from nodules and teardrops to angular and flake-shaped with variable sizes. 4 Rice body formation is a common complication of rheumatoid arthritis but can also occur without any underlying systemic disorder.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations